Advanced Receiver Autonomous Integrity Monitoring (ARAIM) for Unmanned Aerial Vehicles - Snijders, M.; Engwerda, H.J.A.; Fidalgo, J.; Dominguiz, E.; Moreno, G.; Duque, J.P.; Martinez, J.; Martini, I.; Sgammini, M.; Boyero, J.P. (MDPI, 2023)
Advanced Receiver Autonomous Integrity Monitoring (ARAIM) is an evolution of the currently used aviation-focused Global Navigation Satellite System integrity service, Receiver Autonomous Integrity Monitoring (RAIM). Where RAIM supports only lateral navigation, with its adaptations including multiple frequencies and constellations, and with the use of Integrity Support Messages (ISMs), ARAIM also supports vertical guidance. Although these techniques were designed to serve the aviation community, ARAIM could be used in a wide range of applications, especially safety-critical applications. With further evolutions, ARAIM could also be extended to cover more demanding applications in various sectors. This work reports the outcomes of the study of the applicability of ARAIM for the Unmanned Aerial Vehicle (UAV) sector. Keywords: integrity; ARAIM; GNSS; UAV; HAS; sensor fusion